Entrepreneurial Development and its Learning Process: Evidence from Indonesia (Journal of Business Management and Accounting, 2014)
The paper offers an understanding of the process of entrepreneurial learning that is critical to the development of entrepreneurs and entrepreneurship. The paper reveals the relationship between entrepreneurial learning process and the success of the business among small-scale entrepreneurs for selected learning types. The materials for analysis were obtained from a field work conducted in Surakarta, Indonesia by using a survey method. Four hundred and eighty-five 485 respondents were identified based on stratified random sampling for urban, suburban and rural areas. The total population identified was 1,040 small entrepreneurs. The reliability of the research instrument was 0.9, which is considered high. It was found that the types of learning, i.e., formal, non-formal and informal, had different effects on the learning process of small-scale entrepreneurs. Such findings are important to the development of the entrepreneurial learning and policy to improve the effectiveness of entrepreneurship development program.